The Aotus nancymaae erythrocyte proteome and its importance for biomedical research (2017)
The Aotus nancymaae species has been of great importance in researching the biology and pathogenesis of malaria, particularly for studying Plasmodium molecules for including them in effective vaccines against such microorganism. In spite of the forgoing, there has been no report to date describing the biology of parasite target cells in primates or their biomedical importance. This study was thus designed to analyse A. nancymaae erythrocyte protein composition using MS data collected during a previous study aimed at characterising the Plasmodium vivax proteome and published in the pertinent literature. Most peptides identified were similar to those belonging to 1189 Homo sapiens molecules; > 95% of them had orthologues in New World primates. GO terms revealed a correlation between categories having the greatest amount of proteins and vital cell function. Integral membrane molecules were also identified which could be possible receptors facilitating interaction with Plasmodium species. The A. nancymaae erythrocyte proteome is described here for the first time, as a starting point for more in-depth/extensive studies. The data reported represents a source of invaluable information for laboratories interested in carrying out basic and applied biomedical investigation studies which involve using this primate. Significance An understanding of the proteomics characteristics of A. nancymaae erythrocytes represents a fascinating area for research regarding the study of the pathogenesis of malaria since these are the main target for Plasmodium invasion. However, and even though Aotus is one of the non-human primate models considered most appropriate for biomedical research, knowledge of its proteome, particularly its erythrocytes, remains unknown. According to the above and bearing in mind the lack of information about the A. nancymaae species genome and transcriptome, this study involved a search for primate proteins for comparing their MS/MS spectra with the available information for Homo sapiens. The great similarity found between the primate's molecules and those for humans supported the use of the monkeys or their cells for continuing assays involved in studying malaria. Integral membrane receptors used by Plasmodium for invading cells were also found; this required timely characterisation for evaluating their therapeutic role. The list of erythrocyte protein composition reported here represents a useful source of basic knowledge for advancing biomedical investigation in this field. © 2016 Elsevier B.V.